Screenwriting - Horton, Andrew 1944- (Behind the silver screen series, 2014)
"Reaching back to the early days of Hollywood, when moonlighting novelists, playwrights, and journalists were first hired to write scenarios and photoplays, Screenwriting illuminates the profound ways that screenwriters have contributed to the films we love. This book explores the social, political, and economic implications of the changing craft of American screenwriting from the silent screen through the classical Hollywood years, the rise of independent cinema, and on to the contemporary global multi-media marketplace. From The Birth of a Nation (1915), Gone With the Wind (1939), and Gentleman's Agreement (1947) to Chinatown (1974), American Beauty (1999), and Lost in Translation (2003), each project began as writers with pen and ink, typewriters, or computers captured the hopes and dreams, the nightmares and concerns of the periods in which they were writing. As the contributors take us behind the silver screen to chronicle the history of screenwriting, they spotlight a range of key screenplays that changed the game in Hollywood and beyond. With original essays from both distinguished film scholars and accomplished screenwriters, Screenwriting is sure to fascinate anyone with an interest in Hollywood, from movie buffs to industry professionals"--Publisher information.